Radio’s Role in Digital Information Dissemination - Nurhasanah Haspiaini; Mira Aditia Widianti (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
The rapid development of digital audio platforms has challenged conventional radio broadcasting. Previous studies have largely examined radio and podcasts separately. This study addresses this gap by examining how Motion Radio utilizes podcasts as a strategy for disseminating information in the digital era. This research adopts a qualitative case study approach. Data were collected through in-depth interviews with key informants, direct observation, and documentation of podcast content and production practices at Motion Radio. The unit of analysis includes content curation, production processes, and distribution strategies of radio-based podcasts. Data analysis was conducted using an interactive model comprising data reduction, data display, and conclusion drawing. The findings indicate that Motion Radio strategically curates selected on-air broadcast content, particularly informative and educational programs, into podcast formats to overcome the temporal limitations of radio broadcasting. Podcast production is integrated with live radio programming, enabling efficient content repurposing, although it remains constrained by limited human resources. Podcasts are positioned not merely as broadcast archives but as digital information channels aimed at expanding audience reach beyond conventional radio listeners. In conclusion, the integration of radio broadcasting and podcasting demonstrates a functional transformation of radio within the digital audio ecosystem. This study contributes theoretically by strengthening discussions on media convergence and platformization in audio communication, and practically by providing insights for the radio industry in formulating sustainable digital strategies. Future research is recommended to conduct comparative studies across radio stations, quantitative analyses of podcast content, and audience behavior research in digital audio consumption.